Signal processing and integrated circuits - Baher, H. (Chichester, West Sussex : Hoboken, N.J. : John Wiley & Sons, 2012)
This book provides a balanced account of analog, digital and mixed-mode signal processing with applications in telecommunications. Part IPerspective gives an overview of the areas of Systems on a Chip (Soc) and mobile communication which are used to demonstrate the complementary relationship between analog and digital systems. Part II Analog (continuous-time) and Digital Signal Processing contains both fundamental and advanced analysis, and design techniques, of analog and digital systems. This includes analog and digital filter design; fast Fourier transform (FFT) algorithms; stochastic signa.
Front Matter -- Perspective. Part Introduction -- Analog, Digital and Mixed-Mode Signal Processing -- Analog (Continuous-Time) and Digital Signal Processing. Part Introduction -- Analog Continuous-Time Signals and Systems -- Design of Analog Filters -- Discrete Signals and Systems -- Design of Digital Filters -- The Fast Fourier Transform and its Applications -- Stochastic Signals and Power Spectra -- Finite Word-Length Effects in Digital Signal Processors -- Linear Estimation, System Modelling and Adaptive Filters -- Analog MOS Integrated Circuits for Signal Processing. Part Introduction -- MOS Transistor Operation and Integrated Circuit Fabrication -- Basic Integrated Circuits Building Blocks -- Two-Stage CMOS Operational Amplifiers -- High Performance CMOS Operational Amplifiers and Operational Transconductance Amplifiers -- Capacitors, Switches and the Occasional Passive Resistor -- Switched-Capacitor and Mixed-Mode Signal Processing. Part Introduction -- Design of Microelectronic Switched-Capacitor Filters -- Non-Ideal Effects and Practical Considerations in Microelectronic Switched-Capacitor Filters -- Integrated Sigma-Delta Data Converters: Extension and Comprehensive Application of Analog and Digital Signal Processing -- Answers to Selected Problems -- References -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Signal processing -- Equipment and supplies; Signal processing -- Mathematics; Integrated circuits -- Design and construction; Electric filters; Signal processing -- Equipment and supplies; Signal processing -- Mathematics; Integrated circuits -- Design and construction; Electric filters; COMPUTERS -- Information Theory; TECHNOLOGY & ENGINEERING -- Signals & Signal Processing; Electric filters; Integrated circuits -- Design and construction; Signal processing -- Equipment and supplies; Signal processing -- Mathematics; Signal processing / Equipment and supplies; Signal processing / Mathematics; Integrated circuits / Design and construction; Electric filters; Electronic books; Electronic books